Reflective teaching skills of experienced and inexperienced physics teachers [electronic resource] - Fariba Mirzaei, 1975-, author 530747; Fatin Aliah Phang Abdullah, 1980-, supervisor 490583; Fakulti Pendidikan 8185 (2014)
Thesis (Ph.D (Pendidikan Fizik)) - Universiti Teknologi Malaysia, 2014